Development of Butter Cookie with Fiber from Pomelo Albedo - ปุณเกษม ดร.นราธิป (Journal of Food Health and Bioenvironmental Science, 2016)
The objectives of this research were to study the effect of supplemental pomelo albedo at 3 levels of 3, 6 and 9% (w/w flour basis) on physical, chemical, microbiological and sensory qualities of butter cookies. It was demonstrated that the addition of albedo did not affect the hardness of butter cookies. Conversely, the albedo addition led to L* increase, and a* and b* decrease. Chemical analysis of butter cookies showed that the albedo addition led to increase in dietary fiber, but decreased the lipid and carbohydrate content. Moreover, the albedo addition did not affect microbiological quality including total plate counts, yeast and mold counts and this product conformed to the Thai community product standards. However, addition of albedo had an effect on the flavour of cookies. Results of sensory evaluation showed that the 9% (w/w) albedo addition to butter cookies was mostly accepted with 7-8 point rating on a 9-point Hedonic preference scale. The estimated shelf life of butter cookies with added albedo was also studied, qualities of the 9% (w/w) albedo addition butter cookies packed in a polypropylene pouch at 30 ํC including moisture content, hardness and thiobarbituric acid (TBA) test were analyzed. An increased storage time led to increase in moisture content and decrease in hardness of the cookies due to the moisture transfer between the cookies and air. In addition, TBA values increased with the storage time. The 9% (w/w) albedo supplemented butter cookies could be stored for 10 weeks at room temperature before reaching threshold TBA values, while the control product (no albedo) could only be stored for 9 weeks. This might be due to higher lipid content of the control condition that led to oxidation reactions.